2020
DOI: 10.2147/ppa.s236794
|View full text |Cite
|
Sign up to set email alerts
|

<p>Feasibility and Acceptability of an mHealth-Based Approach as an HIV Prevention Strategy Among People Who Use Drugs on Pre-Exposure Prophylaxis</p>

Abstract: Introduction: There has been increasing interest in the use of mHealth technology in health care. To our knowledge, however, there is a lack of empirical evidence on the utilization of text messaging services (short message service; SMS) for HIV prevention among opioiddependent people who use drugs (PWUD). As part of our formative work, we conducted an in-depth feasibility and acceptability study on the use of SMS reminders for HIV prevention in this risk group. Methods: Forty HIV-negative, opioid-dependent PW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
(54 reference statements)
0
12
0
1
Order By: Relevance
“…Two studies described successful PrEP initiation and monitoring using an online platform [ 17 , 27 ], and four studies found that telehealth for PrEP was feasible, acceptable, and effective [ 13 , 16 , 24 , 25 ]. Eight studies examined the use of apps [ 11 , 18 , 21 , 28 ] and SMS [ 15 , 19 , 22 , 26 ] for PrEP service delivery. Of note, only one study, the Enhancing PrEP in Community Settings (EPIC) study, presented results from an RCT [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies described successful PrEP initiation and monitoring using an online platform [ 17 , 27 ], and four studies found that telehealth for PrEP was feasible, acceptable, and effective [ 13 , 16 , 24 , 25 ]. Eight studies examined the use of apps [ 11 , 18 , 21 , 28 ] and SMS [ 15 , 19 , 22 , 26 ] for PrEP service delivery. Of note, only one study, the Enhancing PrEP in Community Settings (EPIC) study, presented results from an RCT [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Methods to further promote and monitor service engagement and adherence include sign-posting within target communities (item A22) and peer support work by community members (A25–26). Digital health tools, especially mobile phone apps, also show promise for this purpose (A24) 33–35. For example, the Refaid app (https://refaid.com) shows migrants and refugees the location of nearby services.…”
Section: Resultsmentioning
confidence: 99%
“…Dentro de estos mismos objetivos que tienen las intervenciones se encuentra el que las personas se realicen pruebas de detección de VIH, de tal manera que conozcan su estado serológico y más aún si han tenido conductas sexuales de riesgo, ya que como se ha observado no todas las personas tienen este hábito (Shrestha et al, 2020); también en los últimos años ha cobrado gran relevancia el uso de PrEP como una alternativa en la que las personas pueden tomar una pastilla cuando han tenido alguna conducta de riesgo sexual para prevenir la infección por VIH (Camlin et al, 2020).…”
Section: Discussionunclassified